Regional differences in breakfast in a hotel chain in Brazil (Research, Society and Development, 2022)
There is no more intimate relationship than that of man with the act of eating. What you eat, how you eat and where you eat define which food culture you are in. The intrinsic relationship between tourism and gastronomy has always occurred, but little noticed or studied in academic works. This survey aimed to compare the culinary preparations offered for breakfast in a hotel chain in Brazil and to identify differences in regional cuisine, in order to gather evidence that there are regional differences in Brazil and that these differences were initially marked by indigenous cultures. African and Portuguese and more recently by foreigners from different regions of Europe, hybridizing with our culinary values, contributing to the regionalization of breakfast. This peculiar fact of consumption demonstrates that breakfast in hotels is an untapped potential for the national hotel trade.